OUTSPREAD PATTERN SIMULATION SYSTEM OF SEPTICAEMIA EPIZOOTICA DISEASE USING CELLULLAR AUTOMATA METHOD IN NUSA TENGGARA TIMUR - Muslimah, Leni (LPPM of STIMIK ESQ, 2018)
Ngorok disease (Septicaemia Epizootica) is a disease that attacks livestock, especially cows are acute and very fatal. Nusa Tenggara Timur is a livestock producer in Eastern Indonesia, one of them is in Kabupaten Kupang. Therefore, the people of NTT are more dominant in raising cattle. However, these livestock animals are susceptible to various diseases, especially SE. Prevention SE is done by vaccination on each cow in the NTT region. Therefore, this study was conducted to help simulate the pattern of Septicaemia Epizootica disease pattern using Cellullar Automata. In the CA simulation there are several stages to be passed that is data collection, data selection process, cartograp making and then the formation of CA simulation. The CA simulation process is performed using the Von Neumann R1 formula that applies an adjacent neighboring scheme of 4 neighbors. From the results of this study obtained a level of accuracy of 77% based on pattern simulation from 2014 to 2016. Therefore this application can already be used to simulate SE disease spread pattern in the coming years.